Peningkatan Kreativitas Anak Usia Dini melalui Permainan sebagai Edukasi Media Belajar Kreatif di PAUD Kabupaten Karawang - Ditha Prasanti; Sarah Aisha (Universitas Mataram, 2023)
Kindergarten (PAUD) as a second learning vehicle after the family environment for early childhood, gives a distinct impression for those who experience it. As a place to play while learning that is full of educational values, it should provide varied learning. Especially in the current digital era, early childhood learning media must also be developed. This is the reason we carry out Community Service (PkM) activities targeting early childhood children in an early childhood education center located in Ciparagejaya village, Karawang district. Its location close to the coast, becomes a learning vehicle for the people who are there. Therefore, we also carried out PkM activities with the title